2016
DOI: 10.1140/epjd/e2016-70438-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of sodium and cesium on aggregates of C60

Abstract: Abstract.We explore the formation of C60 sodium and C60 cesium complexes in superfluid helium nanodroplets. Anomalies in mass spectra of these doped droplets reveal anomalies in the stability of ions. (C60)mCs + n ions (m 6) are particularly abundant if they contain n = 6m + 1 cesium atoms; (C60)mCs 2+ n dications (m 3 or 5) are abundant if n = 6m + 2. These findings are consistent with the notion that alkali metal atoms (A) transfer their valence electrons into the three-fold degenerate lowest unoccupied orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 60 publications
6
12
1
Order By: Relevance
“…In these early works, they found for lithium certain "magic numbers" which can only arise from an homogeneous distribution of twelve Li atoms on the top of the pentagonal faces of fullerene. Some other elements were found to form clusters above a certain concentration, or to form other non-homogeneous distributions on the surface [18,19,20,21,22,23]. This behavior is detrimental for hydrogen adsorption, because the clustering of the metal atoms on the surface of C 60 reduces the active adsorption sites for H 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…In these early works, they found for lithium certain "magic numbers" which can only arise from an homogeneous distribution of twelve Li atoms on the top of the pentagonal faces of fullerene. Some other elements were found to form clusters above a certain concentration, or to form other non-homogeneous distributions on the surface [18,19,20,21,22,23]. This behavior is detrimental for hydrogen adsorption, because the clustering of the metal atoms on the surface of C 60 reduces the active adsorption sites for H 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…We did not notice these features in our previous report on heavily coated C 60 cluster cations, but close inspection of Figure 1 in that report reveals a steep rise in the ion abundance of (C 60 ) m Cs n + from n = 4 to 5 followed by a plateau, for m = 2, 3, and 4. 8 The abundance of ions with n ≤ 4 was simply too small to discern any anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report we had measured abundance distributions of (C 60 ) m Cs n + cations containing up to six C 60 and several dozen Cs. 8 Local maxima in the ion abundance suggested that ions with n = 6 m + 1 are particularly stable. 22 The findings were consistent with earlier research by Martin and co-workers on potassium- and rubidium-doped fullerene aggregates; the authors suggested the presence of C 60 A 6 building blocks in which the alkali metal atoms transfer their valence electrons to the 3-fold degenerate lowest unoccupied orbital (t 1u ) of the fullerene, forming essentially ionic bonds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations